(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Electricity is one of the most important things in our daily lives. However, most Filipinos cannot access or afford to possess electricity in their everyday lives. Most of the research stated that many Filipinos are affected by not being able to acquire electricity in their daily lives. To address the aforementioned issue, the researchers conducted a study to find an alternative source of energy to generate electricity. They used neodymium magnets and wind energy as the alternative sources of electricity. The results of this study were highly acceptable as assessed by both electricians and mechanical engineers in terms of materials, while acceptable in terms of procedures, mechanisms, and presentation. It indicates the significant difference between the assessments of the two groups of respondents on the level of acceptability of magnetic and wind energy. The acquired mean of electricians is 3.15, while mechanical engineers have an acquired mean of 3.14. The variance for electricians is 0.334, while that for mechanical engineers is 0.197. The t-computed value is 2.306, while the t-critical value is 0.196, with an alpha level of 0.05 and a degree of freedom of 8. As a result, it accepts Ho. The researchers suggested finding a suitable mini fan blade for their model, using a stronger magnet and a large battery capacity, reducing the size of the box, and adding a cover on the mini fan blade for safety handling.